Stormbound - Alvarez, Jennifer Lynn (Alvarez, Jennifer Lynn. Guardian Herd, 2015)
Star has moved his herd of refugee pegasi to the coast to escape the Mountain Herd and the bitter memories of the past, and as head stallion it is up to him to protect and lead them--but the freezing storms of winter are coming, old enemies are seeking revenge, and an ancient adversary has awoken from sleep.